Editorial Note (American Journal of Islam and Society, 1986)
This issue of the MISS introduces a format of five sections. The initialsection, on Islamization of knowledge, consists of three articles. The firstarticle was written by the late Lamya’ al-Faruqi, slain wife of al-Shahid Ismailal-Faruqi, who interprets the Islamization of knowledge through the soundarts. We hope her provocative analysis will trigger responses from ourknowledgeable readers. The second paper, by the distinguished Pakistanischolar, Professor Akbar Ahmed, treats us to a lengthy analysis of anthropologicalknowledge from the perspective of the scholar interested in itsIslamization. The third article in this section, by Professor Masudul AlamChoudhury, raises serious issues in the microeconomic foundations of Islamiceconomics.The second section is a symposium on political governance. It consists ofsome ’ijtihad by Muhammad Salahuddin on the limits of political obedienceand a shorter account by Farhang Rajaee of the discrepancy between politicalideal and reality in the little-researched Late-Classical period of Muslim history.Another symposium in the next issue, consisting of articles by Hasan Turabiand Muna Abdul-Fadl, covers the implications for change in societal institutionsand in the ’Ummah generally.The middle section of this issue is a position paper by Sayeed al Seini, whogives us his interpretation of the Islamic concept of news. This area of researchis beginning to occupy the attention of Muslim students of communications,and we hope more papers will be published in future issues.The fourth section consists of two research notes. The first one, by ProfessorMushtaqur Rahman, looks at the Afghan conflict and analyses the wayit may affect the future of Central Asian Muslims in the “pivot of Asia” duringthe 1980’s and beyond. This issue is of great concern to all Muslims aroundthe world. The second note, by Hasan A. Yahya, examines the conflict ofsecularization and tradition, especially as it affects women, reflected in reading textbooksin Jordan, Libya, Saudi Arabia, and Syria. Using content analysis,the author identifies the main factors that in his opinion are responsible forthis development.The final section, of literature reviews, starts with an article by MuhammadBenaboud on Orientalist treatment of Revelation and the Prophet’s Sira,some of which has made some constructive contribution to the study of theMuslim world. professor Benaboud’s paper may encourage others to scrutinizeclosely contemporary Orientalist scholarship, in order to counter disinformationand to develop Islamic leadership in the study of comparative religion ...